Pengaruh Fashion Involvement dan Shopping Lifestyle terhadap Pembelian Impulsif Produk Fashion di Shopee - Marbun, Enjelina; Meutia, Riza Fanny (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of fashion involvement and shopping lifestyle on impulsive buying of fashion products on Shopee among civil servants in Onanganjang District. The background of this research is based on the growing use of e-commerce, particularly Shopee, and the increasing phenomenon of impulsive buying triggered by fashion involvement and shopping lifestyles. The research method used is a quantitative approach with a descriptive design. Data was collected through questionnaires distributed to 72 female civil servant respondents who use the Shopee application. Data analysis was performed using multiple linear regression. The results show that fashion involvement has a positive and significant influence on impulsive buying. Similarly, shopping lifestyle also has a positive and significant effect on impulsive buying. Simultaneously, both variables significantly influence impulsive buying behavior. These findings provide implications for fashion business players in developing marketing strategies that align with consumer characteristics in the digital era.